Parental mental health conditions and use of healthcare services in children the first year of life- a register-based, nationwide study - Signe Heuckendorff; Martin Nygård Johansen; Søren Paaske Johnsen; Charlotte Overgaard; Kirsten Fonager (BMC, 2021)
Abstract Background Parental mental health conditions have been associated with increased morbidity and use of healthcare services in offspring. Existing studies have not examined different severities of parental mental health conditions, and the impact of paternal mental health has been overlooked. We examined the association between two severities of parental mental health conditions and use of healthcare services for children during the first year of life and explored the impact of both maternal and paternal mental health conditions. Methods This register-based cohort study included all live-born children born in Denmark from 2000 to 2016. Information on socioeconomics, diagnoses, drug prescriptions, and healthcare contacts was extracted from nationwide public registries. Parents were grouped according to severity of mental condition based on the place of treatment of the mental health condition. Negative binominal regression analyses were performed to estimate the incidence rate ratio (IRR) of contacts to general practice (GP), out-of-hour medical service, emergency room (ER), and out- and inpatient hospital contacts during the first 12 months of the child's life. Results The analyses included 964,395 children. Twenty percent of the mothers and 12 % of the fathers were identified with mental health conditions. Paternal mental health conditions were independently associated with increased risk of infant healthcare contacts (GP IRR 1.05 (CI95% 1.04-1.06) and out-of-hour IRR 1.20 (CI95% 1.18-1.22)). Risks were higher for maternal mental health conditions (GP IRR 1.18 (CI95% 1.17-1.19) and out-of-hour IRR 1.39 (CI95% 1.37-1.41)). The risks were even higher if both parents were classified with a mental health condition (GP IRR 1.25 (CI95% 1.23-1.27) and out-of-hour contacts IRR 1.49 (CI95% 1.45-1.54)), including minor mental health condition (GP IRR 1.22 (CI95% 1.21-1.24) and out-of-hour IRR 1.37 (CI95% 1.34-1.41)). This pattern was the same for all types of healthcare contacts. Conclusions Both maternal and paternal mental health conditions, including minor mental health conditions, were associated with increased utilization of healthcare services. Focus on both parents' mental health conditions (even if minor) may be warranted in service planning.